2020
DOI: 10.1371/journal.pone.0232737
|View full text |Cite
|
Sign up to set email alerts
|

The 2015-2016 El Niño increased infection parameters of copepods on Eastern Tropical Pacific dolphinfish populations

Abstract: The oceanographic conditions of the Pacific Ocean are largely modified by El Niño (EN), affecting several ecological processes. Parasites and other marine organisms respond to environmental variation, but the influence of the EN cycle on the seasonal variation of parasitic copepods has not been yet evaluated. We analysed the relation between infection parameters (prevalence and mean intensity) of the widespread parasitic copepods Caligus bonito and Charopinopsis quaternia in the dolphinfish Coryphaena hippurus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…According to L. González and Carvajal (2003), fluctuations in environment variables, mainly temperature, modify the population dynamics and the distribution of parasitic copepods. This has been recently shown in C. bonito and B. quaternia in the Ecuadorian Pacific Ocean (Santana‐Piñeros et al, 2020), an area with wide temperature changes because of the arrival of the Humboldt current, which produces upwellings of cold, nutrient‐rich deeper water and an increase in trophic activity (Daneri et al, 2000; Graco et al, 2007; Jones, 1998; Okuda et al, 1983), thus favoring the dispersal and occurrence of infective stages of copepods and pelagic fish (ERFEN, 2011). On the other hand, these species of copepods have been recorded in more than a dozen hosts belonging to diverse fish families, such as Carangidae, Istiophoridae, Mugilidae, Sciaenidae, and mainly Scombridae (Cressey & Cressey, 1980; Kabata, 1979; Lester et al, 1985; Rohde et al, 1980; Williams & Bunkley‐Williams, 1996).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…According to L. González and Carvajal (2003), fluctuations in environment variables, mainly temperature, modify the population dynamics and the distribution of parasitic copepods. This has been recently shown in C. bonito and B. quaternia in the Ecuadorian Pacific Ocean (Santana‐Piñeros et al, 2020), an area with wide temperature changes because of the arrival of the Humboldt current, which produces upwellings of cold, nutrient‐rich deeper water and an increase in trophic activity (Daneri et al, 2000; Graco et al, 2007; Jones, 1998; Okuda et al, 1983), thus favoring the dispersal and occurrence of infective stages of copepods and pelagic fish (ERFEN, 2011). On the other hand, these species of copepods have been recorded in more than a dozen hosts belonging to diverse fish families, such as Carangidae, Istiophoridae, Mugilidae, Sciaenidae, and mainly Scombridae (Cressey & Cressey, 1980; Kabata, 1979; Lester et al, 1985; Rohde et al, 1980; Williams & Bunkley‐Williams, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…In Ecuador, C. bonito has been recorded previously in Cratinus agassizii Steindachner 1878 from the Galápagos Islands (Wilson, 1937). Also, Santana‐Piñeros et al (2020) recently reported C. bonito as parasite species of C. hippurus , with a PR fluctuating between 29% and 100%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We did a search in the literature for biological variables related to this periodicity of every 11 and 4.5 months, and we only found that infections in aquatic parasitic copepods ( Ch. Quaternia ) are increased with a periodicity of every 11 and 3 months in the oceanographic conditions of the Pacific Ocean associated with the 2015-2016 El Niño (Santana-Piñeros et al, 2020). The reader may note the parallelism in the periodicity of infection parameters in Ch.…”
Section: Discussionmentioning
confidence: 99%